A Comparison Study the Effect of Doping by Ga2O3 and CeO2 On the Structural and Optical Properties of SnO2 Thin Films - Abood, Maab A.; Hasan, Bushra A. (Iraqi Journal of Science, 2023)
This research deals with the effect of gallium oxide and cerium oxide as dopants on the structural and optical characteristics of tin oxide. Gallium and cerium oxide doped tin oxide was prepared with different doping concentrations (0, 0.03, 0.05 and 0.07) wt. pure and doped tin oxide thin films were prepared by the pulsed laser deposition technique. X-ray diffraction and UV-Visible spectrophotometer were employed to investigate both oxides doping effects. Results showed that all prepared samples have poly-crystalline structure with a preferred plane of crystal growth along (110), where the crystal size grew from 40.3 nm to 64.5 nm and to 43.5 nm for Ga2O3 and CeO2 doped tin oxide thin films, respectively. Transmittance decreased drastically by increasing the doping ratio of gallium oxide. In contrast, it increased by increasing the doping ratio of cerium oxide. The optical energy gap was found to change in nonsystematic sequence with the increase of Ga2O3 doping concentration, while it decreased monotonically by increasing the CeO2 doping concentration.